Sự tiến hóa địa động lực khu vực Tây Bắc dựa trên các nghiên cứu đá trầm tích màu đỏ hệ tầng Yên Châu (K2yc) - Chính, Nguyễn Đức; Khiển, Nguyễn Xuân; Thắng, Tạ Trọng (Vietnam Journal of Earth Sciences, 2005)
The red-beds of Yen Chau formation have been subjected to the two stages for supplying sedimentary deposits: * The first stage is corresponding to the lower part of the Yen Chau formation. The main source of supplying debris is essential from rich-in-quartz sedimentary rocks, acidic and basic igneous rocks. The sedimentary materials are mainly coarsegrained, multimineralic sandstones (mainly Litharenite and Subfeldsarenite) which are characterized for passive continental margin settings. * The second stage is corresponding to the higher part of the Yen Chau formation. The main provenance is composed of rich-in-quartz sedimentary rocks and acidic igneous rocks. The coarse-grained sedimentary material such as conglomerates, sandstones bearing polymineralic gravels intercalated with coarse-grained sandstones of bad to medium sorting and medium rounding (mainly Litheranite and Lithic- Feldsarenite) characterizing for re-orogenic settings.